2021
DOI: 10.1080/1744666x.2022.2014323
|View full text |Cite
|
Sign up to set email alerts
|

The infection risks of JAK inhibition

Abstract: Introduction Janus Kinase inhibitors (JAKi) have shown to be highly effective in the treatment of immune-mediated inflammatory diseases. As with all immunomodulatory therapies, careful assessment of any treatment-associated infection risk is essential to inform clinical decision-making. Areas covered We summarize current literature on infection rates among the licensed JAKi using published phase II/III trial results, post-licensing and registry data. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 77 publications
0
31
0
1
Order By: Relevance
“…Patients with RA had a higher risk of serious infection than those with AD or AA during treatment with baricitinib, possibly because 79% and 51% of these former patients were also receiving methotrexate or glucocorticoids, respectively, [ 91 ] and they tended to be, on average, older than patients receiving the drug for dermatological diseases (Table 2 ). Increased vulnerability to serious infection with age is well established [ 118 ] and this was further shown in the baricitinib safety data [ 111 ]. Winthrop et al [ 111 ] also showed that the risk in baricitinib-treated patients was increased in those with abnormal BMI and in those receiving concomitant glucocorticoid therapy.…”
Section: Adverse Events Of Special Interest: Baricitinib Clinical Evi...mentioning
confidence: 92%
See 3 more Smart Citations
“…Patients with RA had a higher risk of serious infection than those with AD or AA during treatment with baricitinib, possibly because 79% and 51% of these former patients were also receiving methotrexate or glucocorticoids, respectively, [ 91 ] and they tended to be, on average, older than patients receiving the drug for dermatological diseases (Table 2 ). Increased vulnerability to serious infection with age is well established [ 118 ] and this was further shown in the baricitinib safety data [ 111 ]. Winthrop et al [ 111 ] also showed that the risk in baricitinib-treated patients was increased in those with abnormal BMI and in those receiving concomitant glucocorticoid therapy.…”
Section: Adverse Events Of Special Interest: Baricitinib Clinical Evi...mentioning
confidence: 92%
“…The JAK/STAT pathway is involved in immune regulation, thereby modulating defences against infection [ 118 ]. Increased risk of infection versus placebo has been reported with JAKis, with the risk of serious infections being comparable to that of biologics in rheumatologic diseases [ 118 ].…”
Section: Adverse Events Of Special Interest: Baricitinib Clinical Evi...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a known class effect for JAKi is an elevated risk of herpes zoster (67)(68)(69)(70). In one recent study, serious infections were more frequent with tofacitinib at a dose of 10 mg twice daily compared to TNF inhibition (71), which contradicts some available evidence pointing to a similar risk of serious infections under JAKi compared to other biological disease-modifying antirheumatic drugs (bDMARDs) (72,73). The risk for opportunistic infections (herpes zoster, tuberculosis) under tofacitinib in this study was higher compared to a TNFinhibitor, and even more so when tofacitinib dose was 10 mg compared to 5 mg.…”
Section: Type I Interferonopathiesmentioning
confidence: 97%